STAT5 promotes accessibility and is required for BATF-mediated plasticity at the Il9 locus - Yongyao Fu (Nature Communications, 2020)
BATF is a transcription factor that is needed for IL-9 production by T helper 9 cells. Here the authors show that STAT5 is needed at the Il9 locus to enable BATF to function in this manner and that this interaction can reprogram other T helper subsets into IL-9 producing cells, thus regulating the immune response to disease.